2012
DOI: 10.1016/j.jecp.2010.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Mooney faces by young infants: The role of local feature visibility, contrast polarity, and motion

Abstract: We examined the ability of young infants (3- and 4-month-olds) to detect faces in the two-tone images often referred to as Mooney faces. In Experiment 1, this performance was examined in conditions of high and low visibility of local features and with either the presence or absence of the outer head contour. We found that regardless of the presence of the outer head contour, infants preferred upright over inverted two-tone face images only when local features were highly visible (Experiment 1a). We showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 52 publications
4
32
0
Order By: Relevance
“…Dannemiller and Stephens (1988) and Mondloch et al (1999) consistently reported that 12 week olds, but not 6 weeks olds or newborns, preferred schematic faces with positive contrast polarity over contrast reversed versions of the same stimuli. In addition, and again consistent with Farroni et al (2005), Otsuka, Hill, Kanazawa, Yamaguchi, and Spehar (2012) reported that a preference for upright over upside-down two-tone facial images disappeared when the contrast polarity of the stimuli was reversed. The disappearance of an upright face preference for contrast reversed stimuli suggests that the "faceness" of the facial images may be lost when contrast polarity is reversed.…”
Section: Introductionsupporting
confidence: 72%
“…Dannemiller and Stephens (1988) and Mondloch et al (1999) consistently reported that 12 week olds, but not 6 weeks olds or newborns, preferred schematic faces with positive contrast polarity over contrast reversed versions of the same stimuli. In addition, and again consistent with Farroni et al (2005), Otsuka, Hill, Kanazawa, Yamaguchi, and Spehar (2012) reported that a preference for upright over upside-down two-tone facial images disappeared when the contrast polarity of the stimuli was reversed. The disappearance of an upright face preference for contrast reversed stimuli suggests that the "faceness" of the facial images may be lost when contrast polarity is reversed.…”
Section: Introductionsupporting
confidence: 72%
“…This observation is supported by developmental studies showing that contrast polarity is essential for face detection in newborns (Farroni et al, 2005) and older infants (Otsuka et al, 2012). From a neurofunctional point of view, in adults, there is an increased latency and amplitude of the face-sensitive N170 ERP component (Bentin et al, 1996;Rossion & Jacques, 2011 for a review) to negative polarity faces (Itier & Taylor, 2002;Tomalski & Johnson, 2012).…”
Section: Introductionmentioning
confidence: 71%
“…Although one can argue that only a limited number of object categories have been tested, the consistency of the contrast polarity effect with a wide variety of ''face'' stimuli points towards specificity. More specifically, the deleterious effect of contrast negation has been demonstrated with realistic faces of different degrees of familiarity (unfamiliar, e.g., Liu et al, 1999; famous, e.g., Gilad, Meng, & Sinha, 2008; personally familiar, e.g., Bruce & Langton, 1994; experimentally familiarised, e.g., Galper, 1970) to simplified two-tone faces (i.e., Mooney faces, George et al, 1999;Otsuka et al, 2012;Phillips, Jenkins, & Morris, 1972) and even schematic stimuli arranged in a crude face-like configuration (i.e., two eyes and a mouth, Tomalski et al, 2009;Farroni et al, 2005). Both infant preference (Farroni et al, 2005;Otsuka et al, 2012) and monkey neurophysiology (Ohayon et al, 2012) show that positive contrast polarity is essential to elicit a preferential response for face/facelike stimuli.…”
Section: Specificity Of Contrast Polarity Asymmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…According to this requirement, when the contrast polarity of the shadows and nonshadows is reversed, the perception of the shadows should collapse, and, consequently, the 3-D information should also collapse. In the domain of face perception, Otsuka, Hill, Kanazawa, Yamaguchi, and Spehar (2012) showed effects of contrast polarity on infants' perception. They found that 3-to 4-month-old infants preferred to view an upright two-tone face rather than an inverted two-tone face.…”
mentioning
confidence: 99%